2013
DOI: 10.1136/jnnp-2013-305323
|View full text |Cite
|
Sign up to set email alerts
|

Controlled general anaesthesia for subthalamic nucleus stimulation in Parkinson's disease

Abstract: Our results confirm that STN stimulation performed under controlled GA is efficient and has similar short-term and long-term motor effects than intervention under local anaesthesia. Furthermore, this specific procedure is not associated with more adverse events. The success of such an intervention requires strict anaesthetic monitoring and accurate STN identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 39 publications
4
66
1
1
Order By: Relevance
“…Nevertheless, the starting point, namely the dosage in the 22 patients of the standard group is concordant with calculations based on the published mean dosage of 50–67 µg/kg/min for conscious sedation [9, 13, 17]. Also, the higher propofol dose in the first 4 patients with intubation corresponds to the dosage generally used for anaesthesia induction (2 mg/kg) and total intravenous anaesthesia (10 mg/kg/h) [3]. The reason for including patients preceding the intervention group as a “standard group” for comparison, although heterogeneous and smaller in size (but from the same hospital), was to cover the wide spectrum of protocols that are in clinical practice, besides calculating the doses of sedatives and analgesics from that information in the literature.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Nevertheless, the starting point, namely the dosage in the 22 patients of the standard group is concordant with calculations based on the published mean dosage of 50–67 µg/kg/min for conscious sedation [9, 13, 17]. Also, the higher propofol dose in the first 4 patients with intubation corresponds to the dosage generally used for anaesthesia induction (2 mg/kg) and total intravenous anaesthesia (10 mg/kg/h) [3]. The reason for including patients preceding the intervention group as a “standard group” for comparison, although heterogeneous and smaller in size (but from the same hospital), was to cover the wide spectrum of protocols that are in clinical practice, besides calculating the doses of sedatives and analgesics from that information in the literature.…”
Section: Discussionsupporting
confidence: 61%
“…Hypertensive reactions in attacks of anxiety or panic have been described, as well as ischaemic heart attacks [32]. Respiratory distress, limited or disrupted cooperation and hallucinations have been described and listed as indication for general anaesthesia [3]. DBS surgery is a special and challenging situation for patients, especially for compromised PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical limitation in our understanding of anesthetic best practices is that only a few studies have quantified the effect of anesthetics on MER [14,41,44,45], although a number have qualitatively assayed it, suggesting that too much sedation degrades the MER quality [13,14,15,20,39,41,42,43,44,46,47,48,49,50,51,52,53,54]. Considering those studies that quantified the effects on MER, we do know that some were affected by anesthetic choice, for example, during propofol sedation, background population activity within the STN, as well as FR, was reduced [13,14,41,43,44,51], REMI combined with ketamine demonstrated a reduction in background activity with preserved neuronal FRs [45], and REMI alone had no effect [41].…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up assessments were performed by the same neurologist one year post-surgery (in 188 patients), with a five years follow-up accomplished in only 65 patients. Authors concluded that this particular anesthesia technique did not affect short-term and longterm motor outcomes [44].…”
Section: General Anesthesiamentioning
confidence: 99%